# What are the factors of(4x+6)^2 - (2y-2)^2?

### 2 Answers | Add Yours

(4x + 6)^2 - (2y - 2)^2

This shows the Difference of Squares Pattern.

Allow a to represent (4x + 6).

Allow b to represent (2y - 2)

According to the Difference of Squares Pattern:

a^2 - b^2 = (a + b)(a - b)

Therefore...

(4x + 6)^2 - (2y - 2)^2 = (4x + 6 + 2y + 2)(4x + 6 - 2y + 2)

**Simplified factors: (4x + 2y + 8)(4x - 2y + 8)**

This is a difference of two squares that returns the product:

a^2 - b^2 = (a-b)(a+b)

Let a = 4x + 6 and b = 2y - 2

a - b = 4x + 6 - 2y + 2 = 4x - 2y + 8

a + b = 4x + 6 + 2y - 2 = 4x + 2y + 4

**The requested factors are:(4x+6)^2 - (2y-2)^2 = (4x - 2y + 8)(4x + 2y + 4).**